An analysis of railway track behaviour based on distributed optical fibre acoustic sensing. (August 2020) - Milne, David; Masoudi, Ali; Ferro, Edgar; Watson, Geoff; Le Pen, Louis
Highlights: φ-OTDR DAS strain measurement allowing long fibres and high sample rates. Spatial and temporal rail strain under train loading from field trials. Analytical evaluation of the load-deflection behaviour of railway track using a single system. Abstract: Trackside monitoring of railways provides useful data for understanding the condition and mechanical behaviour of railway track, prior research has shown that railway track performance varies significantly along its length, primarily owing to changing support conditions. Understanding the changing performance along track offers the potential for improved track design and maintenance. Different technologies are used to investigate this. For example, inertial sensors, or high-speed filming with digital image correlation (DIC) for track deflection, and traditional strain gauges for loads. The latter usually rely on in-situ calibration. These techniques are suitable for measurements at discrete locations along the track length but are not suited to measuring performance variability even along a few hundred meters of a railway line. This paper investigates the use of a recently developed sensing system known as distributed acoustic sensor (DAS) that uses optical fibres. This method has the potential to be used over very long lengths of track; offers high sample rates; and has a gauge length and spatial resolution suitable for investigating the load-deflection behaviour of the track. This study presents DAS optical fibre strain measurements from a study site and presents novel methods for determining the rail deflection and the load per sleeper end. The DAS results are compared with point location measurements using a traditional strain gauge and deflections determined using imaging and DIC. The DAS system offers reliable distributed strain measurement that convert to estimates of track deflection and load with the potential for continuous spatial and temporal coverage over significant lengths of track.